PENANGANAN STUNTING SEBELUM DAN SESUDAH PANDEMI COVID-19 DI PROVINSI BALI - Titis Krisnawati (Universitas Udayana, 2021)
The stunting prevalence rate in 2019 was low in Bali Province. However, there are still two regencies in this province where the prevalence rate is above the WHO reference limit of maximal 20 percent, which is Buleleng Regency (22.05%) and Bangli Regency (23.01%). Stunting handling during the COVID-19 pandemic encountered several obstacles that could affect the stunting prevalence rate. Therefore, this study aims to assess the level of stunting handling before and after the COVID-19 pandemic at the regency/municipalities level in Bali Province by constructing The Stunting Handling Special Index (IKPS), which includes five dimensions and ten indicators. The result of the study found that the IKPS rate in most of the regency/municipalities in Bali Province has decreased. The decrease in the IKPS rate is concerned could increase the stunting prevalence. The IKPS rate also decreased in Buleleng Regency and Bangli Regency, specifically in the health, education, and social protection dimension. Indicators that have declined in Buleleng Regency are the percentage of birth attendants by health workers at health facilities, modern family planning, early childhood education, utilization of health insurance, and recipients of social protection cards/prosperous family cards. Meanwhile, indicators that have decreased in Bangli Regency are immunization, modern family planning, exclusive breastfeeding, early childhood education, and utilization of health insurance.